THE READABILITY OF READING TEXTS IN ENGLISH TEXTBOOKS FOR THE EIGHTH GRADE STUDENTS IN MEDAN IN THE ACADEMIC YEAR OF 2015/2016 - Barli Kifli; Meisuri (Universitas Negeri Medan, 2016)
This study focused on the readability of reading texts in English textbooks for grade VIII students in Medan in the academic year of 2015/2016. This study attempted to find out whether the English reading texts were appropriate or not in terms of the readability level for the target students. This study was categorized as descriptive qualitative research. The source of the data were six reading texts which consist of descriptive, recount and narrative texts selected from three English textbooks entitled English for Junior High School VIII published by Mediatama, English on Sky 2 published by Erlangga, and English in Focus published by Pusat Perbukuan Departemen Pendidikan Nasional, for grade VIII in Medan which were designed under guidance of Kurikulum Tingkat Satuan Pendidikan (KTSP). The Dale and Chall original formula was used to analyze the data from the textbooks. The findings of the study showed that the average readability score of the six texts in English in Focus textbook was 6.0. It indicated that the reading texts in English in Focus textbook is appropriate for the eighth grade students since it’s level is for the seventh and eighth grade. The average readability score of reading texts in English on Sky and English for Junior High School VIII textbook were 5.7 and 5.5. The scores indicated that the reading texts in both English on Sky and English for Junior High School VIII textbook were too easy for the eighth grade students since the textbooks’ level was for the fifth and sixth grade.